Kitchen and table: Duty and Pleasure of Women (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The women had a fundamental obligation to care for the family and home. One of his main occupations was the power of her husband, their children and the group of people who were family. Buy the food, cook, serve at the table were tasks that filled much of his time. The women of the lower classes should engage personally, but also women of the upper classes were required to direct the work. But what was a must and sometimes a burden, could also be a pleasure. Many women were good cooks and transformed their work in a rewarding experience and some transmitted this knowledge through writing, even to the publication of books.
Keywords: Women; feeding; book recipes.